Of ligths and shadows: Projections and Revelations (ARQUISUR Revista, 2022)
This reflection article starts from an old debate on the real possibilities of knowing the sensible world from our senses. The reflection is made from examples, developed in the field of representation: art and architecture that show that many times the limitations of our ability to perceive objects can be transformed into creative resources by the talent of their authors. Some of these works are nods to these limitations and remind us that what we perceive, as we do, does not necessarily correspond to the real object that gives rise to the sensitive image.The examples analyzed here are openings to our conventional way of observing that reveal to us that reality can be very different from what we think we see.Artists and architects use these differences to amaze us and make us doubt the scope of our knowledge, formed from our sensations and our culture based on experience and reason. It is enough for this to break the hermeneutical system in which we are used to contrasting things so that these works teach us and provoke us a deep reflection.
Keywords: architecture, plastic arts, projections, perception, representation